The Early‐Middle Miocene subduction complex of the Louisiade Archipelago, southern margin of the Woodlark Rift - Laura E. Webb; Suzanne L. Baldwin; Paul G. Fitzgerald (Geochemistry, Geophysics, Geosystems)
Abstract Field, microstructural, and 40Ar/39Ar thermochronologic data from the Louisiade Archipelago, the southern rifted margin of the Woodlark Basin in SE Papua New Guinea, document an accretionary wedge that formed during Early‐Middle Miocene N‐dipping subduction of the Australian margin and transpression along the Australian‐Pacific plate boundary. Metasedimentary rocks of the Calvados Schist and the metagabbros that intrude them were metamorphosed at up to greenschist‐facies conditions. Three tectonic foliations (S1–S3) are present and F1–F3 fold hinges plunge ESE or WNW, parallel to mineral, stretching, and intersection lineations. Fold vergence is dominantly to the SW, and top‐to‐the‐SW thrusting of ultramafic rocks over the Calvados Schist is documented locally on Rossel Island. The data suggest progressive deformation associated with NNE‐SSW shortening and ESE‐WNW extension via dissolution‐precipitation creep and, more locally, dislocation creep. 40Ar/39Ar step‐heating analyses of three white mica separates yield Middle Miocene plateau or plateau‐like segments that are affected by variable Pliocene argon loss and are interpreted as syntectonic mica growth during metamorphism and deformation followed by partial resetting just prior to the onset of seafloor spreading in the Woodlark Basin. A ∼12 Ma 40Ar/39Ar age from a dacite sill of the Panarora Volcanics provides a minimum age constraint for the termination of northward subduction and a maximum age for crosscutting brittle strike‐slip faults. These data are critical to constraining the subduction‐exhumation history of the world's youngest high‐ultrahigh‐pressure terrane and further support analogies between SE Papua New Guinea and the Early Oligocene Western Alps.